Evaluation of Blood Mercury Levels and Creatinin Levels in Indonesian Traditional Gold Miners in Central Java - Wimpy, Wimpy; Widhiyastuti, Endang; Puspitasari, Lala (GLOBAL HEALTH SCIENCE GROUP, 2024)
Based on the world gold council data in 2024, Indonesia is the eighth largest gold producing country in the world. More than 200 gold mining locations spread throughout Indonesia, but gold mining processes in Indonesia especially in Central Java are still carried out traditionally. The importance of this research is that traditional gold mining can lead to health issues such as mercury poisoning and impaired kidney function wich is characterized by the increased of creatinine levels Purpose : to evaluate the blood mercury levels and creatinine levels in Indonesian traditional gold miners in Central Java. Methods : This research uses a cross-sectional analitycal method. The number of samples in this research was 20 gold miners as respondents using a quota sampling technique. Data on blood mercury level results were obtained by examining blood mercury levels with a mercury analyzer and creatinine levels were obtained by examining serum creatinine with a photometer. The spearman’s rho test is used to test the correlation between blood mercury and creatinine levels. Results : As many as 19 out of 20 respondents had mercury levels of more than 20 µg/L, exceeding the threshold set by NCBI but they all had creatinine levels that were still within normal limits according to the NCBI limits wich is less than 1,2 mg/dL. The results of the Pearson correlation test obtained a sig. value (2 tailed) 0,962 where it can be concluded that there is no correlation between blood mercury levels and creatinine levels in.